'1.5°C to stay alive': climate change, imperialism and justice for the Caribbean. Issue 11 (2nd November 2017) - Sealey-Huggins, Leon
Abstract: Treating the threat of climate change in the Caribbean as a case study instructive for responses globally, this article examines the social and political relations of climate change. It argues for an analysis taking into account the ways in which the histories of imperialism and colonialism have shaped contemporary global 'development' pathways. The article charts how Caribbean vulnerability to temperature rises of more than 1.5°C of warming comprise an existential threat structured by contemporary social relations that are imperialist in character. Hope can be taken from a politics of climate justice which acknowledges the climate debts owed to the region.